2013
DOI: 10.1101/pdb.top078824
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Analysis of Mouse and Human Cancer Genomes

Abstract: Fundamental advances in our understanding of the human cancer genome have been made over the last five years, driven largely by the development of next-generation sequencing (NGS) technologies. Here we will discuss the tools and technologies that have been used to profile human tumors, how they may be applied to the analysis of the mouse cancer genome, and the results thus far. In addition to mutations that disrupt cancer genes, NGS is also being applied to the analysis of the transcriptome of cancers, and, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…As regards an appropriate cancer model, in addition to similar pathological phenotypes it is highly expected that the model also carries comparable molecular features and follows same carcinogenesis progress with its cognate human cancer type 5 . Several investigations focusing on the molecular features of AOM/DSS model were implemented, which reported some common features shared by human and mouse CRC, such as mutation or deregulation of KRAS 6 and CTNNB1 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…As regards an appropriate cancer model, in addition to similar pathological phenotypes it is highly expected that the model also carries comparable molecular features and follows same carcinogenesis progress with its cognate human cancer type 5 . Several investigations focusing on the molecular features of AOM/DSS model were implemented, which reported some common features shared by human and mouse CRC, such as mutation or deregulation of KRAS 6 and CTNNB1 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…GEMMs are also indispensable in preclinical studies to test new drugs in immunocompetent animals [26]. Thus, cross-species analyses provide a powerful tool to pinpoint genes conserved across both species that are master regulators of tumor development [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…A number of genetically engineered mouse models (GEMM) of prostate cancer have been developed, and triangulating the findings from genome-wide expression datasets from human cancers with those from well-characterised mouse models may provide a useful filter to prioritise genes that are functionally important to cancer development (Robles-Espinoza & Adams, 2014). Previous studies in various cancer types have demonstrated that integration of gene expression or copy number alteration data from human and murine tumours is a viable approach to derive diagnostic, prognostic or predictive signatures (Belmont et al, 2014) and to identify candidate driver genes (Ellwood-Yen et al, 2003;Tompkins et al, 2013).…”
Section: Introductionmentioning
confidence: 99%